The Effect of Group Counseling Services on Increasing the Confidence and Learning Motivation of Broken Home Students - Khadafi, Ziqki Rifki; Abdurrahman; Darmayanti, Nefi (Ilomata International Journal of Social Science, 2024)
A broken home is a situation in which parents or one of them has divorced or no longer lives together, which can affect a child's psychological and academic development. This study aims to determine the influence of counseling services on increasing the confidence and learning motivation of broken home students. The research method used is quantitative research with pre-test and post-test control group design experiments. The results of the study showed that there was a significant increase in the confidence and learning motivation of students who received group counseling services compared to the control group, this was evidenced by the results of the normality test with a pretest significance value of the gis value (0.098) > 0.05, then H0 was accepted so that the data was distributed normally, while the Posttest, The value of sig. (0.094) > 0.05. Then with the results of the t-test, it was found that the tcount value of the SPSS result was -13.477 and ttable obtained a value of 2.110 so that the tcount < ttable, H0 was rejected, then H1 was accepted. So it can be concluded that Group Counseling Services have a significant influence on increasing the Learning Motivation of Broken Home students.